Faktor-Faktor yang Mempengaruhi Kinerja pada Balai Besar Sumber Daya Lahan Pertanian (BBSDLP) Bogor - Syah, Zahir; Sukmawati, Anggraini (Universitas Brawijaya, Indonesia, 2016)
The employee performance is a major factor for the organization in achieving organizational goals. There are several factors that affect employee performance improvement such as through training, qualification and competence. With training, qualification and competence of employees is expected to increase the knowledge, expertise, skills and attitudes to be able to carry out duties in a professional position with based on personality and ethics in officials in accordance with the needs of agencies in carrying out the tasks given to him. This research aimed to determine: (1) to analyze the role of training on the perfprmance Bbsdlp Cimanggu Bogor, (2) to analyze the role qualification on the performance Bbsdlp Cimanggu Bogor, (3) to analyze the role of competence on the performance Bbsdlp Cimanggu Bogor, (4) to analyze the role of Training, qualification and competence on The performance BBSDLP Cimanggu Bogor. This Research using two types of data is primary and secondary, while the research methode involves two variabel is: The Independent variabel (training,qualification and competence), and the dependen (employee performance). The Population size is taken as 75 samples. This analysis using the multiple linear regression analysis. This research conclude: training, qualification, competence and simultaneously positive and significant impact on the performance Bbsdlp Cimanggu Bogor,is evident from the results of calculation of that t is highest than ttable .